PROGRESSIVE METHOD OF COTTON REGENERATION - Khuramova, Khadicha (Scientific and Technical Journal of Namangan Institute of Engineering and Technology, 2024)
According to the conducted research, the main working parts of the device when extracting fly beads from waste in operating regenerator machines are the sawn-off drum knives and the grate grid, and their location, shape, and influence on each other affect the cleaning. In the devices used, the grate shape is cylindrical. During the operation of the device in the separation of fly beads from waste, cutting off fly beads from mixed waste with the maximum possible efficiency depends on the grate's geometric shape and the blades' location.